2022
DOI: 10.1021/accountsmr.2c00154
|View full text |Cite
|
Sign up to set email alerts
|

Uniting Heat and Light in Heterogeneous CO2 Photocatalysis: Optochemical Materials and Reactor Engineering

Abstract: Conspectus The rapid increase in atmospheric CO2 concentration (∼420 ppm) has become one of the significant issues threatening human survival. As an effective measure to solve this major problem, renewable energy-powered catalytic CO2 conversion technologies have received vast attention in both academia and industry. Among these techniques, photothermal catalysis is a rising star with promising potential for CO2 conversion even under milder conditions. Indium oxide was among the first to be used in phototherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
(236 reference statements)
0
7
0
Order By: Relevance
“…8 The generation of heat arises from the nonradiative relaxation of light-induced charge carriers on In 2 O 3 . 26,27 The presence of alkylsilanes establishes a thermal insulating layer, effectively curbing thermal conduction and augmenting the local temperature of S2 by approximately 12 °C. 28,29 Nonetheless, even when compared to the S0 sample tested in the dark at 242 °C, the S2 sample tested at 200 °C under light still exhibits a significantly higher methanol production rate, with an increase of ∼464 μmol g cat −1 h −1 (Figure S14C).…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…8 The generation of heat arises from the nonradiative relaxation of light-induced charge carriers on In 2 O 3 . 26,27 The presence of alkylsilanes establishes a thermal insulating layer, effectively curbing thermal conduction and augmenting the local temperature of S2 by approximately 12 °C. 28,29 Nonetheless, even when compared to the S0 sample tested in the dark at 242 °C, the S2 sample tested at 200 °C under light still exhibits a significantly higher methanol production rate, with an increase of ∼464 μmol g cat −1 h −1 (Figure S14C).…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…Meanwhile, the thermal effect is manifested through an increase in system temperature, which may be attributed to non-radiative relaxation of semiconductors, 14,15 localized heating induced by plasma, 16−18 thermal vibration of molecules, 19 as summarized in our previous work. 20 It is noteworthy to distinguish the subtle differences from the definitions of "photochemistry" and "thermochemistry," "photochemical" and "photophysical" effects, and "photochemical" and "photothermal" effects in other studies. 13,21−24 Obviously, there is currently growing evidence that synergistic mechanisms in non-thermal and thermal effect are of particular interest.…”
Section: Introductionmentioning
confidence: 98%
“…It is concluded that light excitation generates highenergy carriers to participate in the reaction, thereby promoting the activation of reactants, reducing the reaction energy barrier, adjusting the reaction paths, and maintaining catalytic activity. 20 Nevertheless, thermal and non-thermal effects do not always synergistically promote the reaction. In the photoexcitation process of semiconductors, without effective carrier transfer path, the temperature increased by the thermal effect will accelerate the carrier recombination, which is not conducive to the photothermal synergistic reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Inspired by these observations, FLP sites have been created on CeO 2 and In 2 O 3 surfaces to activate H 2 , CO 2 , H 2 O, etc. 7,15,16 However, the rigid solid lattice and lack of effective strategies to manipulate Lewis acid-base interaction have restricted the optimization of heterogeneous FLPs.…”
mentioning
confidence: 99%